An Institutional and Fiscal Analysis of Foreign Worker Compensation Fund (DKPTKA) Management in Developing Indonesian Workforce Competence - Roza, Hendry (Jurnal Ketenagakerjaan, 2025)
The use of foreign workers in Indonesia not only affects the dynamics of the labour market, but also contributes fiscally through the Foreign Worker Compensation Fund (DKPTKA) as part of Non-Tax State Revenue (PNBP). Regulatory provisions, as stipulated in Government Regulation No. 34 of 2021, Articles 33-35, direct the DKPTKA to support the enhancement of Indonesian workers' competencies through training, certification, and the strengthening of vocational training institutions. However, this study found that the current utilization of the DKPTKA is not yet fully in line with these strategic objectives, as most of its allocation is still directed towards job expansion programs and administrative activities. This article aims to provide a factual overview and policy analysis related to the utilization of DKPTKA, examine its compliance with regulatory provisions, and formulate relevant policy recommendations for optimising the use of DKPTKA in a more effective and oriented towards improving the competence of the Indonesian workforce.Through policy analysis and comparison with practices in several countries such as the Philippines, Thailand, Vietnam, Malaysia, and the UAE, this study shows that foreign worker compensation funds have the potential to be a strategic instrument for local workforce capacity building. Based on these findings, this article recommends reorienting the allocation of DKPTKA towards competency development, integrating technology transfer in the use of foreign workers, providing incentives for local governments, diversifying sources of non-tax state revenue from employment, and strengthening impact-based monitoring and evaluation systems.